White matter microstructural alterations in amblyopic adults revealed by diffusion spectrum imaging with systematic tract-based automatic analysis. Issue 4 (29th May 2018) - Tsai, Tzu-Hsun; Su, Hsien-Te; Hsu, Yung-Chin; Shih, Yao-Chia; Chen, Chien-Chung; Hu, Fung-Rong; Tseng, Wen-Yih Isaac
Abstract : Background/aim: We investigated the microstructural changes in white matter of adults with amblyopia using diffusion spectrum imaging with systematic tract-based automatic analysis of the whole brain. Methods: Ten adults with amblyopia (six women and four men, 33.6±10.6 years old on average) and 20 age- and sex-matched normal-sighted controls were enrolled. The mean generalised fractional anisotropy (GFA) was measured in 76 white matter tracts and compared between the experimental and control groups using a threshold-free cluster-weighted method and t -test. A 2-percentile cut-off was used to identify segments with the greatest differences between the two groups. Results: Participants with amblyopia had significantly lower GFA values than the controls in 11 segments located in nine white matter tracts, which included the following: left arcuate fasciculus, left frontal aslant tract, left fornix and left inferior fronto-occipital fasciculus of the association fibres; left thalamic radiations of the auditory nerve and bilateral optic radiations of the projection fibres; and genu and middle temporal gyrus of the callosal fibres. Amblyopic participants had statistically higher GFA values in the bilateral uncinate fasciculus than those of the controls. Conclusion: This preliminary study using whole-brain tractographic analysis of white matter reveals association between abnormal early visual processing and alterations in brain architecture, which may be related to various higher-level deficits, such as audiovisual integration and hand−eye coordination in patients with amblyopia.